Macrozoobenthos Diversity at Mangrove Rehabilitation Area, Tangerang Regency: - Ai Solihat; Ario Damar; Fery Kurniawan (Masyarakat Moluska Indonesia, 2023)
Tangerang Regency has continued to rehabilitate its coastal ecosystems, especially mangrove areas that have been converted into ponds and abandoned. One of the functions of the mangrove ecosystem is as a habitat for biota, including macrozoobenthos. This study aimed to analyze mollusc diversity in the mangrove rehabilitated area in Tangerang. Macrozoobenthos sampling was carried out from February to March 2022 in Ketapang Villag (station 1), Patramangala Village (station 2), and Tanjung Pasir Village (station 3), by applying a 1×1 m2 quadratic transects. The mollusks found were from the class bivalves and gastropods. In general, mollusk abundance is the number of individual mollusks in an area. The composition of the mollusk species found were bivalves (42%) and gastropods (58%). The highest diversity index, uniformity index, and dominance index from the three villages were 1,8882, 0,6294, dan 0,5183. Based on the results of the study showed that the rehabilitation of mangroves is able to become a habitat for mollusks with a fairly high diversity. This is a good indication of the success of rehabilitation and ecosystem health. Key words : bivalves, gastropods, mangroves, mollusca, Tangerang